Noble Ideals in Teaching Profession: Making of an Enviable Enterprise out of the Education Industry in Nigeria - ADEBANJO, Gbenga; KANU, Abednego Chibuzor (Ilorin Journal of Education, 2025)
The paper addressed a number of issues that affect the teacher, the teaching profession and the education industry from the Nigeria perspective. It is a position paper that beamed searchlight on factors of contemporary significance in selecting and training those who choose to make an enterprise of teaching. The ethics and ethos that make teaching a rewarding enterprise for livelihood and achievement of the goal-4 target of the Sustainable Development Goals were discussed. Possible answers were provided to some pertinent questions as it pertains to teachers and teaching. It is an uphill task to achieve a promising future in edupreneurship without competent, motivated, and well-equipped teachers. The various disquieting hurdles - real, imaginable and unimaginable complexities that rear their ugly head on the teachers’ track to success were brought to the limelight. Position and prospects of the teacher in the midst of other seemingly high-class professionals who stick out their shoulders in pride as to the prestigious and lucrative nature of their job are projected. Considering the ongoing transformation in the education industry occasioned by the ‘new normal’ and brought about by the post-pandemic era through digital and technological innovations, the restoration of the teachers’ damaged glory is essential in Nigeria. As the mother of other professions, teachers hold the key to the nation’s socio-economic transformation. Among other recommendations, making teaching a lifelong enterprise involves training, re-training, and re-orientation of teachers’ mindset for knowledge, skills and competencies needed to impart learners and their community towards self-actualization and productivity.